A model for corporate sustainability practices: case study of Malaysian aviation industry (FRGS16-026-0525) - Zakaria, Zamzulaila; Zakaria, Zarina; Amran, Azlan (2019)
Adopting a mixed-method approach, this study has conducted survey, interview and document review of transportation industry generally and aviation industry specifically. The findings of this study are divided into two categories. Firstly, we would summarise findings based on surveys of the roles of internal auditors on enterprise risk management (ERM) implementation in the context of transportation industry in Malaysia. Secondly, we will summarise the findings on the corporate sustainability practices of Malaysian Aviation Industry.